Conceptual Idea of Natural Mechanisms of Recognition, Purposeful Thinking and Potential of Its Technical Application - Rabinovich, Zinoviy L.; Belov, Yuriy A. (Mechanisms, Symbols, and Models Underlying Cognition, 2005)
In general, this paper concerns the topic “From Artificial to Natural”, namely the subject “Computational Neuroscience” (with emphasis on the subsubject “Plasticity”), as well as the subject “Neuro-informatics” (with emphasis on the subsection “Neurostimulators”). The paper also includes some basic considerations and real examples related to the topic “From Natural to Artificial”, namely the subject “Bio-inspired Circuits and Mechanisms” (“Electronics” and “Sensory and motor prostheses”).